Eksistensi Pendidikan Islam Multikultural Era Society 5.0 - Hani' Ni'matul Ula Hani' (Pascasarjana IAIN Ponorogo, 2024)
Multicultural Islamic education is education that is sunnatullah in nature related to diversity and efforts of Islamic education to prevent conflicts in life. The purpose of this research is to answer the existence and role of multicultural Islamic education to face the development of the times in the era of society 5.0. The method used in this study is Library Research , which is by collecting various information about multicultural Islamic education in the Society 5.0 era from various sources as a consideration for making conclusions. The result of this research is that multicultural Islamic education must be able to face the challenges of each era. As well as the challenges in the era of society 5.0 which are oriented towards the rapid use of technology as well as to meet the needs, interact and support socio-economic activities of a multicultural society. With multicultural Islamic education, people can choose good solutions to face a life full of diversity in accordance with the challenges of the times.